The fiery angel - Prokofʹev, Sergej Sergeevič 1891-1953 (Naxos Rights (Europe) Ltd., 2021)
Sergey Prokofiev's operatic tragedy was never performed in the composer's lifetime, the music's brittle energy, drama, and eloquent lyrical tenderness would re-emerge in his Third Symphony. The narrative focuses relentlessly on Renata, who is haunted by an angel who turns out to be the devil. Director Emma Dante describes the opera as an explosive mix of fantastical realism and endless confusion of nightmares, madness, sexual impulses, and cultural clashes', and this Teatro dell Opera di Roma production was acclaimed as ₁a presentation of Prokofiev's masterpiece which sparkles in all its grotesque glory.'
Opera in five acts; libretto by the composer on the novel by Valery Bryusov
Bildformat: 16:9
Keywords: Operas; Filmed performances; Film; Blu-Ray-Disc